Ecologia da polinização e biologia reprodutiva de Ipomoea bahiensis Willd. no semi-árido brasileiro - Pacheco Filho, Alípio José de Souza (2010)
The study of floral ecology is pivotal to understanding the relationships between flowers and their visitors, as well as to understand the role of this interaction in reproductive success and maintenance of plant population. In this study, it was investigated the morphology, floral biology and breeding system of Ipomoea bahiensis Willd. and the interactions between its flowers and the guild of floral visitors. The research aimed mainly to understand the ecological and evolutionary relationships between I. bahiensis and anthophilous insects. For this, methods were used to analyze the functional morphology of flowers, the relationship of floral morphology and biology with visitors, the frequency and behavior these animals, the requirement for pollen and the rate fruit/flower and, finally, was estimated pollen limitation. To increase knowledge about the floral ecology were observed extranupcial nectaries’s visitors and its relation to floral enemies. From the analysis of the data, it was observed that the flowers of I. bahiensis have attributes predominantly psycophily, however they present plasticity in pollination systems, and can also be pollinated by small bees. The dynamics of nectar herewith with the period of stigma receptivity seeks to ensure the visitation of butterflies in this period. However, the variation in the frequency of floral visitors was understood from the availability of pollen, because the main visitors were bees pollen collecting. Pollination tests showed that the reproductive system is xenogamous, dependent on biotic vectors and presents self-incompatibility. It was also observed that the plant is limited by pollen.